Noninvasive 4D pressure difference mapping derived from 4D flow MRI in patients with repaired aortic coarctation: comparison with young healthy volunteers - Rengier, Fabian; Eichhorn, Joachim; Tengg-Kobligk, Hendrik von; Ley-Zaporozhan, Julia; Kauczor, Hans-Ulrich; Ley, Sebastian (The international journal of cardiovascular imaging, 2015)
To assess spatial and temporal pressure characteristics in patients with repaired aortic coarctation compared to young healthy volunteers using time-resolved velocity-encoded three-dimensional phase-contrast magnetic resonance imaging (4D flow MRI) and derived 4D pressure difference maps. After in vitro validation against invasive catheterization as gold standard, 4D flow MRI of the thoracic aorta was performed at 1.5T in 13 consecutive patients after aortic coarctation repair without recoarctation and 13 healthy volunteers. Using in-house developed processing software, 4D pressure difference maps were computed based on the Navier-Stokes equation. Pressure difference amplitudes, maximum slope of pressure amplitudes and spatial pressure range at mid systole were retrospectively measured by three readers, and twice by one reader to assess inter- and intraobserver agreement. In vitro, pressure differences derived from 4D flow MRI showed excellent agreement to invasive catheter measurements. In vivo, pressure difference amplitudes, maximum slope of pressure difference amplitudes and spatial pressure range at mid systole were significantly increased in patients compared to volunteers in the aortic arch, the proximal descending and the distal descending thoracic aorta (p < 0.05). Greatest differences occurred in the proximal descending aorta with values of the three parameters for patients versus volunteers being 19.7 ± 7.5 versus 10.0 ± 2.0 (p < 0.001), 10.9 ± 10.4 versus 1.9 ± 0.4 (p = 0.002), and 8.7 ± 6.3 versus 1.6 ± 0.9 (p < 0.001). Inter- and intraobserver agreements were excellent (p < 0.001). Noninvasive 4D pressure difference mapping derived from 4D flow MRI enables detection of altered intraluminal aortic pressures and showed significant spatial and temporal changes in patients with repaired aortic coarctation.